وضع مؤشرات لتخمین کلف مشاریع مبانی المنشآت المخزنیة - nan, nan; nan, nan; nan, nan (Iraqi Journal of Civil Engineering, 2007)
The estimating of the preliminary costs of any suggested project is the essential base to determine the required budget which needs an experience and some previous data about the projects which constructed in the past but these data are not available for the Iraqi contracting companies , they depending on a few simple storage building . This research consists of study and analysis of fifty different size of storage building which had been built during (1994-2003). The differences in cost between these building are studied too, by comparing the cost between every building against other building. Depending on the available data and field study, the storage building is classified according to proposed conditions. As result there are suggested cost indices for the storage building, also the researcher use mathematical equations to determine the indices and the preliminary cost. The results of applying evaluation show the great ability in determining the preliminary cost